The Effect of Health Education Using Video Media on Increasing Knowledge of Pregnant Women About Low Birth Weight (LBW) in the Penyinggahan Primary Health Center - Raudah, Raudah; Jasmawati, Jasmawati; Nulhakim, Lukman (Rifa'Institute, 2022)
Introduction: The proportion of LBW in Indonesia reaches 6.2%. The World Health Assembly (WHA) targets a reduction in the incidence of LBW in 2025 by 30%. Objective: The purpose of this study is to determine the effect of providing health education using the video method on increasing knowledge of pregnant women about LBW in the working area of the Penyinggahan primary Health center. Methods: The design used in this study was a quasi-experimental study with a one-group pre and post-test design. The data collection instrument uses a questionnaire that has been tested for validity and reliability. The population and sample in this study were pregnant women who had a pregnancy check (ANC) at the Penyinggahan primary Health centeras many as 38 respondents. Data analysis using the Wilcoxon test. Results and Discussion: there is a significant difference between the level of knowledge about LBW before and after being given health education using video with the results of the analysis p-value of 0.000<0.05. Conclusion: There is an effect of health education on increasing knowledge of pregnant women about LBW. With the results of this study, it is hoped that it can be considered by the health center to take policies in terms of increasing knowledge using video tools so that it can increase mother's knowledge to prevent the occurrence of LBW